Kidney Transplant allocation in Portugal - A Lima, Bruno (2013)
[ENG] Factors such as: patient age, place of residence, socioeconomic status, cause of kidney failure, prognosis, duration of dialysis and co-morbidities influence transplantation outcome. Also the quality of available donors must be taken into account when looking for the balance between utility and justice. In the USA, UK and Portugal deceased donor kidney allocation rules are based on systems of points assigned to each possible receptor. However, the key factor in organ allocation is time on dialysis (first come, first served basis). The discussion about access to kidney transplantation with deceased donors never comes to a close and must be done clearly and systematically in order to enable the best decisions at any given moment.